The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/17405904.2013.836114
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm Not Happy, but I'm Ok’

Abstract: Title: "I'm not happy, but I'm ok": How asylum seekers manage talk about difficulties in their host country

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…In both of the extracts discussed thus far, I have demonstrated that, in line with previous work (Goodman et al, 2014;Kirkwood et al, 2013), when accusations of discrimination are made by asylum seekers and refugees in Wales, they are made to appear trivial which avoids making general negative evaluations of the host society. In the next section, however, I present another way in which participants oriented to questions about discrimination, questioning whether incidents of discrimination they had experienced could be attributed to "race.…”
Section: Extract 1 2 Amnasupporting
confidence: 72%
See 3 more Smart Citations
“…In both of the extracts discussed thus far, I have demonstrated that, in line with previous work (Goodman et al, 2014;Kirkwood et al, 2013), when accusations of discrimination are made by asylum seekers and refugees in Wales, they are made to appear trivial which avoids making general negative evaluations of the host society. In the next section, however, I present another way in which participants oriented to questions about discrimination, questioning whether incidents of discrimination they had experienced could be attributed to "race.…”
Section: Extract 1 2 Amnasupporting
confidence: 72%
“…Indeed, the complaints raised in Extracts 1 and 2 pursue this strategy in order to put the experience of discrimination in play whilst avoiding the negative consequences of making accusations of racism (Kirkwood et al, 2013). It is suggested that such strategies also allow the speaker to avoid complaining about the society and appearing ungrateful for the protection which they have received, in line with the findings of Goodman et al (2014) and Kirkwood et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…following Reeves (1983). In addition to denials of racism and disclaimers such as "I'm not a racist, but …" (van Dijk, 1992), deracialisation involves attributing issues with refugee presence in their nations to other factors such as economy (Goodman, Burke, Liebling, & Zasada, 2014), thereby mitigating implications of being against the presence of refugees or asylum seekers in their nations.…”
Section: The Social Psychology Of Migrationmentioning
confidence: 99%